A response to Liz Clark - Drake, H. A. (Scottish journal of theology, 2002)
Elizabeth Clark was characteristically generous and incisive in her comments. She asks six questions, which I will paraphrase as follows: (1) How can we know Constantine's intentions? (2) Did ‘pagan monotheism’ have a broad enough appeal to create the type of constituency Constantine would have needed, and (3) even if it did, would not the turn from ‘cultic practice’ to ‘a system of belief’ – whether pagan or Christian – still have resulted in ‘intolerance and its political analogue, compulsion’? (4) Do I overrate the impact of Julian? (5) ‘Where are the Jews in this discussion?’ (6) Can metaphors based on modern political language and a public policy model be applied to this period without distorting the subject?